Effectiveness, immunogenicity and safety of one vs. two-dose varicella vaccination：a meta-analysis - Mingjuan Yin; Xiaojia Xu; Yaping Liang; Jindong Ni (Taylor & Francis Group, 2018)
Background: Despite high 1-dose vaccination coverage, breakthrough varicella infections still occur. Therefore, 2-dose vaccination is recommended to enhance the immune response to the virus. However, the reported incremental vaccine effectiveness (VE) of 2-dose vaccination varies widely among studies. Methods: To determine the overall effectiveness, immunogenicity and safety of one vs. two-dose varicella vaccination, we searched five databases for articles published during 1995-2017. Results: The incremental VE/efficacy of 2-dose vaccination was 79% (95% confidence interval [CI]: 56%−90%) in randomized controlled trials，63% (95% CI: 36%−79%) in cohort studies and 81% (95% CI: 65%−90%) in case-control studies. Regarding immunogenicity, the pooled standardized mean differences (SMD) of geometric mean titer (GMT) and the pooled relative risk (RR) of seroconversion for 2-dose vs. 1-dose vaccine were 562.44 (95% CI: 471.78-653.10) and 1.03 (95% CI: 1.02-1.04), respectively. Children who received second dose vaccination were at increased risk of grade 3 redness (RR: 4.93, 95% CI: 1.89 − 12.87) and swelling of any intensity (RR: 1.34, 95% CI: 1.08 − 1.66). Conclusions: Two-dose varicella vaccination resulted in higher levels of immunogenicity and provided superior protection than 1-dose vaccination. Safety profiles showed 2-dose vaccination was well tolerated but the incidence of grade 3 redness and of any intensity was significantly higher.